A flexible blue light sensitive organic photodiode with high properties for the applications in low‐voltage‐control circuit and flexion sensors. Issue 2 (23rd January 2014) - Li, Dong; Liu, Xiaohui; Dong, Guifang; Duan, Lian; Zhang, Deqiang; Zhao, Haoyan; Wang, Liduo; Qiu, Yong
<x xml:space="preserve">Abstract</x> Low‐voltage‐control circuit is one of the most important parts of the modern electrical control system due to the avoidance of operation risk and easy automation. Here, based on a C60: m‐MTDATA bulk heterojunction, a blue‐light‐sensitive organic photodiode (OPD) is explored for the development of flexible low‐voltage‐control circuit. The control of circuit under 2000 V high voltage is achieved. The influences of the organic‐layer thickness, the donor/acceptor volume ratio and the matching of energy levels on the photocurrent are investigated. The maximum light/dark current ratio and current transfer ratio of 1.3 × 104 and 1.3% are achieved, respectively. The highest photoresponse is up to 130 mA/W, markedly higher than some commercial inorganic photodiodes. This device could also be used as flexion and mechanical force sensors with the current density changing under different bending conditions. Therefore, this sort of OPD has a promising application in low‐voltage‐controlled, high‐voltage‐endurable hands for intelligent robots. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>